Vapor Phase Electrochemistry 3: Preparation of Metastable Nitrous Acid - Turner, David; Bartlett, Viv (Journal of Scientific Exploration, 2025)
A qualitative electrochemical model for ball lightning was developed during the 1990’s (Turner, 2002). The key requirement was electrochemical refrigeration at the surface of an air plasma. The cooling was shown to result from the conversion of metastable, fully ionized, gas-phase nitrous acid to its stable molecular form. If the refrigeration cools the plasma surface to below 15 0 C, aerosols of nitric acid can be produced in subsequent oxidation processes. These particles restrict the inflow of air toward the plasma and provide the ball with a very effective surface tension. This helps explain several unusual characteristics of lightning balls and also their close relatives, such as earth-lights and Unpredictable Flying Objects. The experiments to be described were undertaken because of their relevance to ball lightning stability, but they also have relevance in other fields of meteorology. They were attempts to reproduce several early observations by C.T.R Wilson that have been largely neglected ever since they were first reported. He irradiated moist, dust-free air with focused beams of ultraviolet light. Using the emission from zinc or cadmium arcs, mists were produced after about 30 minutes of exposure. All our nominally similar experiments failed to produce mists. However, UV radiation from a mercury vapor lamp produced them after a few minutes. The mists contained both nitrous and nitric acid. We also confirmed Wilson’s observations that these mists could be produced at relative humidities slightly below 90%. This is considered impossible according to all models of cloud formation.